PEMIKIRAN POLITIK JAMALUDDIN AL-AFGHANI (Respon Terhadap Masa Modern dan Kejumudan Dunia Islam) - Maryam, Maryam (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2014)
Renewal of Afghani’s Islamic thought was based on the condition of the people and Islamic world, which esperienced social and religious backward. Jamaluddin al-Afghani, together with his Pan-Islamism was able to inspire Muslims and Islamic world to unite and to develop nasionalism among them.